A study of transferrin and ferritin expression in tumor cells of patients with breast cancer - Shepil, O.V.; Lukyanova, N.Y.; Chekhun, S.V.; Polishchuk, L.Z.; Antipova, S.V. (Онкологія, 2014)
Aim: to study and to evaluate the clinical significance of the expression of iron-containing proteins ferritin and transferrin in tumor cells of patients with breast cancer (BC). Object and methods: the study included 143 patients with BC stage II–III. Methods: clinical, morphological and immunohistochemical, statistical. Results: it was shown that BC is characterized by intertumor heterogeneity of expression of transferrin and ferritin. The high degree of differentiation of BC correlates with the lack of expression of transferrin and ferritin. Positive expression of these proteins in the cells of primary tumors correlated with the development of metastases in regional lymphatic nodes. Correlation dependences between parameters of expression of transferrin and ferritin in tumor cells and overall survival in patients with BC have been determined. Conclusions: the expression of transferrin and ferritin may be individual predictive markers of clinical course and survival in patients with BC and one more molecular target for the development of new anticancer agents.